Sustainable and adaptive agile supply chains for resource-based business actors in Indonesia - Latief, Fitriani; Firman, Ahmad; Dirwan, Dirwan; Ilham, Bahrul Ulum (Frontiers in Sustainability, 2026)
Sustainable supply chain research has long suggested that well-designed sustainability practices strengthen business resilience and competitiveness. However, resource-based enterprises in developing economies often operate with severe technological, financial, and managerial constraints, limiting their ability to adopt multiple sustainability initiatives simultaneously. Guided by the Resource Orchestration Theory framework of structuring, bundling, and leveraging resources, this study examined how combinations of internal sustainability practices, supply chain collaboration, and operational agility supported firms in optimising limited resources and adapting to environmental and market volatility. Using fuzzy-set Qualitative Comparative Analysis (fsQCA) on data from 139 resource-based enterprises in Indonesia, the analysis identified six distinct configurations that lead to high sustainability performance. The overall solution consistency (0.82) confirms the reliability of these pathways, while the solution coverage (0.83) indicates that they account for a substantial proportion of the empirical cases exhibiting high performance. Among these pathways, a fully integrated configuration produced the highest raw coverage (0.58), while an externally oriented social-environmental configuration accounted for a raw coverage of 0.52. Notably, one configuration revealed that operational agility was sufficient regardless of the presence or absence of other practices, suggesting its role as a decisive substitutive resource under conditions of resource scarcity. These findings demonstrate that no single practice is universally sufficient; instead, performance improvements emerge from context-specific combinations of internal practices, supply chain collaboration, and agility. This study contributes to sustainable supply chain management literature by emphasising the value of configuration-based strategies for small, resource-constrained enterprises in emerging economies.